School Vision Screening Programs In Reducingchildren With Uncorrected Refractive Error In Low And Middle-income Countries (Lmic)(Systematic Review) - Abraham, Opare (Department of Public Health and Family Medicine, 2020)
Background: The prevalence of uncorrected refractive error among school-age children is on the rise with a detrimental effect on academic performance and socio-economic status of those affected. School vision screening appears to be an effective way of identifying children with uncorrected refractive error so early intervention can be made. Despite the increasing popularity of school vision screening programs in recent times, there is a lot of debate on its effectiveness in reducing the proportion of children with uncorrected refractive error in the long term especially in settings where resources are limited. Objective: To assess the effectiveness of school vision screening programs in reducing children with uncorrected refractive error in LMIC. Search Methods: To identify studies suitable for this systematic review, a comprehensive and systematic search strategy was employed. We searched various databases and the search was restricted to articles published in English. We included RCTs, cross-sectional studies, case-control studies, and cohort studies. Participants included school children who had undergone vision screening as part of school vision screening programs in the LMIC setting and found to have a refractive error. Two independent reviewers screened the result of the search output and performed a full-text review of the search result to identify papers that met the pre-defined inclusion criteria. Data extraction and risk of bias assessment for the included studies was performed by the two independent reviewers and discrepancies were resolved by consensus and through consultation. The certainty of the evidence was assessed using the GRADE approach. Main Result: We found thirty relevant studies conducted in ten different countries that answered our review questions. Our review showed that school vision screening may be effective in reducing the proportion of children with an uncorrected refractive error by 81% (95% CI: 77%; 84%, moderate certainty evidence), 24% (95% CI: 13%; 35%, moderate certainty evidence,) and 20% (95% CI: 18%; 22%, moderate certainty evidence) at two, six, and more than six months respectively after its introduction. Our review also suggest that school vision screening may be effective in achieving 54% (95% CI: 25%; 100%, moderate certainty evidence), 57% (95% CI:46%; 70%, low certainty evidence), 38% (95% CI: 29%; 51%, moderate certainty evidence) and 41% (95% CI: 24%; 68%, low certainty evidence) level of spectacle wear compliance among school children at less than three months, at three months, at six months and at more than six months respectively after its introduction. Our review further found moderate to high certainty evidence indicating that school vision screening together with the provision of spectacles may be relatively cost-effective, safe and has a positive impact on the academic performance of children. Conclusion: Result of this review shows that school vision screening together with the provision of spectacle may be a safe and cost-effective way of reducing the proportion of children with uncorrected refractive error with a long-term positive impact on academic performance of children. Most of the studies included in this review were however conducted in Asia and the applicability of this finding to countries in other regions especially those outside the LMIC circle is not clear.